Limiting the Influence of Regulated Electrical Drainage on Track Circuits - Hrbac, Roman; Kolar, Vaclav; Mlcak, Tomas (Elektronika ir Elektrotechnika, 2018)
For the past two years, the authors of this paper have been working on the development of a new regulated electrical drainage system for tram tracks, which may also be used on railways in the future. When this drainage is used on train tracks equipped with track circuits, it is necessary to make sure that the drainage does not generate current harmonics which may be dangerous for the correct functioning of the circuits. In the Czech Republic, requirements regarding the operation of track circuits are stated by Standard CSN 342613. When the drainage was tested on tram tracks, where there are no track circuits, it was found out that in certain operation modes, the drainage generates frequencies which collide with the frequencies of track circuits. Therefore, a passive filter was designed to solve this problem. With the use of computer simulation and measurements on a laboratory model, it was verified that this filter is able to suppress unwanted current harmonics, so that they are in agreement with the above mentioned Standard. These measurements and simulations are described in this paper. DOI: http://dx.doi.org/10.5755/j01.eie.24.5.21843